Precision Manufacturing of Radio Frequency Microwave Filter Structures Using Additive Manufacturing Technologies - Pattanaik, Nishant; Srinivas, Prajwal (My University, 2025)
There is a growing demand for high-speed communication, to enable this high frequency transmission links are utilized. These links employ microwave radio frequency waveguide filters. Conventional manufacturing of the filters face limitations in producing multi-cavity structures with complex geometries. Additive manufacturing processes offer design freedom, reduced material wastage and rapid prototyping, making it an alternative to produce these filters. This study investigates the feasibility to manufacture the waveguide filters with the frequencies E-Band (65 - 67 GHz) and D-Band (130 - 135 GHz) using two metal Additive manufacturing processes, Binder Jetting Technology (BJT) and Powder Bed Fusion - Laser Beam (PBF-LB). The filters were manufactured using a Markforged PX100™ BJT printer by Bosch GmbH and an EOS M100 PBF-LB printer at Chalmers University of Technology. The BJT filters were printed in two phases, the first was a trial phase to determine the surface roughness measurements that were done on selected surfaces of the parts to determine a suitable orientation for the final print. In the second and final phase, a total of 40 filters were printed, 20 for each band. For PBF-LB, 10 parts were printed 5 for each band. All 40 BJT and 6 PBF-LB filters underwent electrical characterization using a Vector Network Analyzer. Five BJT filters of each frequency bands that reached near-target passband frequency and low loss magnitude were selected for surface treatment with electroless copper plating to improve performance. Results showed that BJT-manufactured E-Band filters achieved insertion losses within the target range while maintaining the required passband frequency, whereas a subset of D-Band BJT filters met the desired specifications. PBF-LB-manufactured filters resulted in higher losses and dimensional inaccuracies due to deviations in internal geometry. The loss magnitudes were reduced by copper plating by nearly half for both E-Band and D-Band filters. Overall, BJT demonstrated greater suitability to manufacture high-frequency waveguide filters